Oficinas de atividades como processos educativos e instrumento para o fortalecimento de jovens em situação de vulnerabilidade social - Trajber, Natalia Keller de Almeida (2010)
Based on the methodology of participatory research, this study was developed with a group of young people who attend one Youth Center on the outskirts of São Carlos (SP), as from the Activities Workshops held there and had as its main subject the analysis of the extending of them in the monitoring of life traces of some of those youngsters, supported in the specific descriptions of some activities. The proposition of the workshops is supported in the theoretical and methodological assumptions of Social Occupational Therapy and the education for freedom advocated by Paulo Freire. Using several resources, it has been constituted as a social technology of approaching, life project (re)construction and the enlargement of the support net for youngsters from urban popular groups in social vulnerability situations. Along the research, we tried to analyze what has been achieved compared to the established aims for the Activities Workshops that have been proposed and implemented by the METUIA‟s Nucleus from the Federal University of São Carlos. The METUIA Project is an interinstitutional group of studies, training and actions for the citizenship of children, adolescents and adults in process of rupture of the social support networks, created by teachers in the area of occupational therapy in three brazilian universities in 1998 with the proposal to develop projects in teaching, research and extension on the social field. We also tried in this study to understand the point of view of the youngsters about their life projects, their (im)possibilities of action and the forging of identities, in this space for reflection and (re)construction of meaning of his being-in-theworld , with potential for transformative action in their immediate contexts, in view of make them strong to face the adverse situations they are exposed. It is concluded that the accumulation of these experiences reveals some repositioning in the lives of youngsters, as well it has contributed to confront contemporary social problems and encouraged them to establish positive links; sociability and familiarity based on mutual respect and solidarity; participation; autonomy; and the reframe of their belonging to scholar environment. It has also provided subsides to discuss about the construction of a formal and non-formal educational propositions supported by democracy, and which carry a tensioning movement of the status quo.